Cloning of royal jelly AccMRJP1 gene from Apis cerana cerana and its expression in Escherichia coli - ZHANG Li-wen; DING Mei-hui; ZHANG Wei-guang; JIN Feng; SHEN Li-rong (浙江大学学报. 农业与生命科学版)
Three clones of AccMRJP1 were screened out from the sequenced brain cDNA library of Chinese honeybee according to the expression sequence tag (EST) of AccMRJP1. Through identifying with polymerase chain reaction (PCR) and sequencing, a AccMRJP1 clone containing an open reading frame (ORF) of 1 302 nucleotides encoding a protein of 433 amino acids was determined. The AccMRJP1 had 99.8% similarity with the previously reported AccMRJP1 sequence (AY279539) in amino acid sequences. The AccMRJP1 was sub-cloned into the prokaryotic expression vector pGEX-4T-2 for fusion expression in Escherichia coli BL21. Analysis result of the SDS-PAGE showed that the expression product contained a specific band of protein about 76 ku in size and accumulated up to about 17.7% of the total bacterial proteins. The fusion protein was cross reactive with glutathione S-transferase (GST) polyclonal antibody and was purified through affinity chromatography, which confirmed the successful expression of GST-AccMRJP1. This work provids a technical base for the utilization of MRJP1 with biological engineering.